The Implementation Of Certainty Factor Method For Diagnosing Diseases In Children - Al-Mubdi, Muhammaad Abid; Siswanto, Siswanto; Fredricka, Jhoanne (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2025)
An expert system is a system in the form of a computer application that seeks to adopt human knowledge in the form of a program with the intention of solving certain problems. Knowledge about something from expert is adopted into an expert system so that the system can diagnose and analyze a problem. Lack of knowledge about childhood diseases such as ARI, diarrhea and Pneumonia, can be fatal to health, therefore to help the community and medical personnel in providing knowledge, consultation and socialization about these diseases is to design and build expert system applications by applying the Certainty Factor method. Expert systems using the Certainty Factor method have the advantage of being able to measure something whether it is certain or uncertain, for example in diagnosing a disease. However, this system also has the disadvantage of only being able to process uncertainty or certainty of only 2 data. The final result of this research is an expert system to diagnose childhood diseases (ARI, Diarrhea, Pneumonia) along with the confidence value of the diagnosed disease, which shows the level of system confidence in the disease.